The importance of using SUUNTO electronic system for monitoring training, in preparation of sportsmen practicing shooting, sample air rifle 10m men - Serban, C.; Tifrea, C. (13th International Scientific Conference eLearning and Software for Education Bucharest, April 27-28, 2017, 2017)
This paperwork would like to emphasize the importance of using SUUNTO electronic system for monitoring training, in the assessment of general and specific training effort, sample Air Rifle 10m 60 shots Men. In the branch of shooting sport, in Romania, the SUUNTO electronic system for monitoring training was used for the first time by athlete Alin George Moldoveanu, Olympic champion - London 2012, sample Air Rifle 10m Men, competitive year 2011 -2012. This system allows the athlete to monitor and analyze his physical and technical trainings in terms of the internal parameters of effort or heart rate, respiratory rate, VO2 max, etc. All this information can be downloaded to a personal computer and the graphical visualization of them can be accessed through site www.movescont.com. Archived information represents important milestones in the shooter`s training, is practically the starting point in achieving preparation plans, according to the current requirements of performance shooting sport. In 2008-2012 Olympic cycle, I personally was part of the technical team of Alin Moldoveanu athlete, as a coach, in charge of physical training. Through the information provided by the SUUNTO monitoring system of training, I could conceive, apply and conduct physical training programs directly targeted on the particularities and needs of the athlete. In conclusion, a physical training well designed and applied, results in a structural and functional adjustment of the body in general and of the heart in particular, being able to reduce the frequency and intensity of the beatings during the elaboration of shooting act (a trained heart beat less often), knowing the fact that the heartbeat is mechanically transmitting vibrations to the rifle.